1996
DOI: 10.1097/00004647-199611000-00033
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Cerebral Venous Thrombosis: Evaluation Using Magnetic Resonance Imaging

Abstract: Summary: Diffusion-weighted (DWI), dynamic contrast enhanced (perfusion imaging), and conventional spin-echo magnetic resonance imaging (MRI) were applied to character ize the pathophysiology of cerebral venous thrombosis (CVT) in the rat. We induced CVT by rostral and caudal ligation of the superior sagittal sinus (SSS) and injection of a thrombogenic cephalin suspension. The resulting pathology was monitored in an acute and long-term study group. Evans blue and hematoxy Iin-eosin staining was performed for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
66
0
5

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(77 citation statements)
references
References 35 publications
6
66
0
5
Order By: Relevance
“…Pathological findings in CVT vary from blood-brain barrier disruption that results in vasogenic edema to obstructive hydrocephalus, perivascular hemorrhage, and ischemic venous infarction with reduced capillary perfusion pressure, which leads to irreversible cytotoxic edema. 5,6 In our case of deep CVT with rapidly declining state of consciousness, early diagnosis was established by CT, MRI, and MR angiography. The intraluminal thrombus was best visible in CT, whereas the hyperacute thrombus could not be detected on MRI because of susceptibility effects.…”
Section: Discussionmentioning
confidence: 85%
“…Pathological findings in CVT vary from blood-brain barrier disruption that results in vasogenic edema to obstructive hydrocephalus, perivascular hemorrhage, and ischemic venous infarction with reduced capillary perfusion pressure, which leads to irreversible cytotoxic edema. 5,6 In our case of deep CVT with rapidly declining state of consciousness, early diagnosis was established by CT, MRI, and MR angiography. The intraluminal thrombus was best visible in CT, whereas the hyperacute thrombus could not be detected on MRI because of susceptibility effects.…”
Section: Discussionmentioning
confidence: 85%
“…10 Alternatively, previous experimental studies showed that retrograde venous pressure might counteract capillary perfusion pressure to decrease cerebral blood flow, and thus cause arterial ischemia resulting in cellular or cytotoxic edema. 12,21 Previous experimental and clinical diffusion-weight imaging studies of cerebral venous thrombosis have shown that ADC value was decreased, 12,22,23 normal, 23 increased, 24 or heterogeneous. 25,26 The ADC values decreased by 56% at 30 minutes after experimental cerebral venous thrombosis, and secondary increases in ADC subsequently developed in a rat model.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental cerebral venous thrombosis in rats has suggested that the balance may depend on the severity as well as the duration of disturbed venous flow. 12 Increased 13,14 and decreased 15 ADC values have also been observed in the brain parenchyma of patients with DAVF, but the pathological conditions caused by disturbed venous flow from CVR associated with DAVFs remain unclear.…”
mentioning
confidence: 99%
“…Previous studies have found that cytotoxic and vasogenic brain edema is consistently associated with acute CVI. 23) This large low-flow area following CVI results not only in angiogenesis but also in increased VP, so edema formation is probably activated by the induction of VEGF expression. Therefore, we suggest that the present animal model was suitable for the evaluation of the relationship be-Neuroprotective Window for Anti-VEGF Therapy in Venous Infarction tween VEGF and brain edema.…”
Section: Discussionmentioning
confidence: 99%